Shear-Induced Transitions between a Planar Lamellar Phase and Multilamellar Vesicles: Continuous versus Discontinuous Transformation - Medronho, B. (2008)
The shear-induced transitions between an oriented lamellar phase and shear-induced multilamellar vesicles (MLVs) in a nonionic surfactant system were studied by deuterium rheo-NMR spectroscopy as a function of time in start-up experiments at several temperatures and shear rates. By starting from an initial state of oriented lamellae and observing the transformation to the final steady state of MLVs and vice-versa, two different mechanisms were found, depending on the direction of the transition and the initial state. The transition is continuous when MLVs are formed, starting from the oriented lamellar phase. On the other hand, a discontinuous nucleation-and-growth process with a coexistence region is observed when transforming MLVs into an oriented lamellar phase.